CEVERO: A soft-error hardened SoC for aerospace applications - Silva, Igor; do Espírito Santo, Otávio; do Nascimento, Diego; Xavier-de-Souza, Samuel (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2020)
Radiation in the space environment poses a constant threat to circuit devices, and, as a solution, several fault tolerance techniques have been developed. However, some techniques use either proprietary technology or radiation-hardening specialized foundries to manufacture, either of which are not easily accessible to most researchers. There is, yet, another set of rad-hard techniques which provide sufficient fault tolerance to specific aerospace applications. The CEVERO SoC is a custom proofof-concept design that implements techniques as lockstep, dual module redundancy and state recovery in its inner fault tolerance module. It is meant to integrate with the open-source PULP platform and to open a path to a full fault-tolerant SoC.